Mangrove Diversity as An Indicator of Ecosystem Health on Ambon Island, Indonesia - Latumahina, Fransina Sarah; Susilawati, Susilawati; Antonius, Antonius; Tewoloipaky, Wasti (Agro Bali : Agricultural Journal, 2024)
The research aims to determine the species richness, diversity and distribution of mangrove populations in forest areas, which is one of the parameters of forest health in the Passo Village’s mangrove forest. It was conducted from July to August 2023 on Ambon Island using the Forest Health Monitoring Field Methods Guide. The research covered 2 hectares of mangrove forest with 3 clusters of 12 observation plots. It was found that seven species of mangroves were found in the area, namely Sonneratia alba,  Rhizophorastylosa, Avicennia marina, Aegiceras corniculatum, Bruguiera gymnorrhyza and Bruguiera parviflora. Cluster 1 had 260 trees. Cluster 2 had 321 trees, and Cluster 3 had 193 trees. The highest value of mangrove species richness was at the sapling level of 1,003. Meanwhile, the species diversity was classified as low at only 0.701 at the seedling level. The highest density of the Sonneratia alba species was 4,290, the species dominance of the Sonneratia alba was 22,240, and the highest importance index occupied by the Sonneratia alba was 160.95. Considering the low level of mangrove forest biodiversity on Ambon Island, rehabilitation and reforestation efforts are needed to maintain the quality and health of the ecosystem, especially in facing the impact of climate change on small islands.